2017
DOI: 10.1080/01431161.2017.1280635
|View full text |Cite
|
Sign up to set email alerts
|

Improved forest-cover mapping based on MODIS time series and landscape stratification

Abstract: Detailed forest-cover mapping at a regional scale by supervised classification is technically limited by various factors. This study evaluates the ability of a landscape stratification method to improve classification accuracy. An object-based segmentation technique (OBIA) was performed to delineate radiometrically homogeneous regions into the study area, used as strata for the classification of a time series of Moderate Resolution Imaging Spectroradiometer (MODIS) normalized difference vegetation index (NDVI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Consequently, the rule-based classification step would largely benefit from the inclusion of an automatic remote sensing-based classification method to produce timely and accurate regional-scale agricultural land-cover maps at the field level. Some studies have shown that partitioning the study region into sub-regions improves the accuracy of regional-scale land-cover classifications [36,37]. Hence, the presented land units' extraction approach could therefore also be used as a preliminary step for automatic remote sensing-based classifications, producing regional-scale land-cover and land-use maps at the field level.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the rule-based classification step would largely benefit from the inclusion of an automatic remote sensing-based classification method to produce timely and accurate regional-scale agricultural land-cover maps at the field level. Some studies have shown that partitioning the study region into sub-regions improves the accuracy of regional-scale land-cover classifications [36,37]. Hence, the presented land units' extraction approach could therefore also be used as a preliminary step for automatic remote sensing-based classifications, producing regional-scale land-cover and land-use maps at the field level.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have attempted to assess the potential of dense high spatial resolution satellite image time series (SITS) for mapping forest types. SITS with very high frequency of observations such as MODIS have been already tested but the coarse spatial resolution of the images makes the tree species identification difficult in the case of complex forest environment [41]. The previous experiments were based on NDVI temporal profiles which help to reduce the data dimensionality but can also limit the discrimination between species.…”
Section: Introductionmentioning
confidence: 99%
“…GEOBIA is not only limited to high resolution images because the approach is not spatial-resolution dependent; therefore, it can be applied to different resolutions if the sizes of the intended objects are compatible with the spatial resolution of the images [44,45]. Thus, GEOBIA has been successfully adopted and implemented to classify MODIS time series data in different applications [44][45][46][47][48][49][50].…”
Section: Object-based Analysis and Image Segmentation Optimisationmentioning
confidence: 99%